Future of cities in Asia: future direction of urban planning, technology and environmental sustainability - Zainol, Rosilawati (Springer nature, 2026)
One of a series of titles on the Futures of Asia, “Future of Cities in Asia” explores diverse facets of Asia's future city landscape during the transformative 2020s, offering insights into pivotal transformations and potential trajectories. The covered topics include the future direction of cities, urban planning, urban design, and climate change. Examining the topics from corporate foresight and past-future to technological trends and environmental shifts, this book showcases a collaborative effort from multidisciplinary researchers navigating the complexities of forecasting and envisioning the futures of Asian cities. This book offers valuable insights into the dynamic discourses on future studies while offering a nuanced understanding of the future city planning possibilities that lie ahead for Asia, as well as deciphering Asia's evolving impact and roles within the broader global context. An insightful read for scholars with an interest in Asian cities and future studies.